2018
DOI: 10.14814/phy2.13840
|View full text |Cite
|
Sign up to set email alerts
|

A 1 week IGF-1 infusion decreases arterial insulin concentrations but increases pancreatic insulin content and islet vascularity in fetal sheep

Abstract: Fetal insulin is critical for regulation of growth. Insulin concentrations are partly determined by the amount of β‐cells present and their insulin content. Insulin‐like growth factor‐1 (IGF‐1) is a fetal anabolic growth factor which also impacts β‐cell mass in models of β‐cell injury and diabetes. The extent to which circulating concentrations of IGF‐1 impact fetal β‐cell mass and pancreatic insulin content is unknown. We hypothesized that an infusion of an IGF‐1 analog for 1 week into the late gestation feta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…In this study, we demonstrated that oIGF-1, like LR3 IGF-1 ( Stremming et al, 2021 ), increased in vitro myoblast proliferation, in vivo myoblast proliferation, and selective fetal organ weight, but it did not increase fetal body weight. Similar to infusion of LR3 IGF-1, fetal oIGF-1 infusion for 1 week also attenuated fetal insulin concentrations, which has been previously reported ( Liechty et al, 1996 ; Lok et al, 1996 ; Boyle et al, 1998 ; White et al, 2018 ; Stremming et al, 2021 ; White et al, 2021 ); however, fetal glucose concentrations in oIGF-1 are maintained similar to control animals. Fetal plasma amino acid concentrations were also lower after infusion of oIGF-1, which is consistent with infusion of LR3 IGF-1 ( Stremming et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In this study, we demonstrated that oIGF-1, like LR3 IGF-1 ( Stremming et al, 2021 ), increased in vitro myoblast proliferation, in vivo myoblast proliferation, and selective fetal organ weight, but it did not increase fetal body weight. Similar to infusion of LR3 IGF-1, fetal oIGF-1 infusion for 1 week also attenuated fetal insulin concentrations, which has been previously reported ( Liechty et al, 1996 ; Lok et al, 1996 ; Boyle et al, 1998 ; White et al, 2018 ; Stremming et al, 2021 ; White et al, 2021 ); however, fetal glucose concentrations in oIGF-1 are maintained similar to control animals. Fetal plasma amino acid concentrations were also lower after infusion of oIGF-1, which is consistent with infusion of LR3 IGF-1 ( Stremming et al, 2021 ).…”
Section: Discussionsupporting
confidence: 82%
“…At the end of the infusion period, fetal IGF-1 concentrations were 3.5-fold higher in oIGF-1 infused fetuses compared to saline infused fetuses ( Figure 3B ). Because IGF-1 infusion decreases fetal insulin concentrations ( Liechty et al, 1996 ; Lok et al, 1996 ; Boyle et al, 1998 ; White et al, 2018 ; Stremming et al, 2021 ; White et al, 2021 ), plasma insulin concentrations were obtained. At the end of the infusion period, fetal plasma insulin concentrations were 89% lower in oIGF-1 infused fetuses compared to fetuses that received a saline infusion ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postnatal myocyte proliferation occurs in skeletal muscle through the engagement and fusion of satellite cells, but cardiac myocyte number is determined prenatally, with minimal regenerative capacity even in the context of injury (White et al, 2018;Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%